PROBLEM-BASED LEARNING (PBL) BASED E-WORKSHEETS ON DIGESTIVE SYSTEM MATERIAL TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS’ CRITICAL THINKING SKILLS - Fitria, Dini; Angrella, Vira; Suciaty, Endah; Annisa, Malika Nurul (Universitas Negeri Medan, 2025)
This research aims to develop and implement an electronic student worksheet based on Problem-Based Learning (PBL) for digestive system material to enhance the critical thinking skills of junior high school students. The PBL model, which emphasizes problem-solving and student-centered learning, is integrated into interactive digital worksheets to facilitate learning anytime and anywhere. This study employed the ADDIE instructional design model, but was limited to the development phase. The validation process involved media and content experts to assess the feasibility of the developed PBL-based E-Worksheet. Validation results indicated that the media aspect received an average score of 77.7%, categorized as feasible, though revisions were needed in supporting images that were deemed less appropriate. Meanwhile, the content aspect obtained a score of 69.4%, also classified as feasible, with suggestions for improvement in learning indicators, images, and supporting videos. Based on these validation outcomes, the PBL-based E-Worksheet was deemed suitable for trial implementation. However, this study was confined to the development stage. Therefore, further research is recommended to evaluate the effectiveness and practicality of E-Worksheet in enhancing students' critical thinking skills.